A parametric study through the modelling of hydrothermal gasification for hydrogen production from algal biomass. (5th March 2021) - Kumar, Mayank; Oyedun, Adetoyese O.; Kumar, Amit
Abstract: Hydrothermal gasification (HTG) is applicable to high moisture content biomass feedstock such as wet microalgae. The key interests of this thermochemical processing are its ability to use whole algae instead of simply lipid extracts and to use a wide range of algal feedstocks. It employs water in the form of a reaction medium to disintegrate biomass into hydrogen gas. The products' composition and yields are a function of process parameters, namely feed concentration, pressure, and temperature. There is very limited literature available on model development to understand the impacts of various input parameters on the products of HTG. This study presents development of a detailed process model for HTG and the illustration of process parameters on the gas product yields. The approach includes developing the system model, identifying the key process parameters in the reactor setup that affect syngas yield, and understanding the overall process in terms of final product yield. A simulation of hydrothermal gasification based on thermodynamic equilibrium is studied. Based on the developed process model about 52.1 t/day of hydrogen can be produced from 500 t/day of wet algal biomass. This shows the potential of large‐scale hydrogen production through this process for hydrogen economy. The results from this study could be used by the gas processing industry and policymakers to determine the most feasible means of converting biomass‐based resources into gaseous fuels.